2008
DOI: 10.1002/asna.200710856
|View full text |Cite
|
Sign up to set email alerts
|

27‐day variations of solar indices and cosmic ray neutron monitor intensities

Abstract: Solar activity indices (coronal, chromospheric as well as photospheric) and cosmic ray neutron monitor rates (different cut-off rigidity) have been used to study 27-day variations in the years from 1957 to 2004. Daily data were employed for this purpose, analysed by the FFT and wavelet techniques. To work with a continuous data set for the cosmic rays (CR), the 'Composite Cosmic Ray' (CCR) set was first created from the observations carried out at different neutron monitor stations. The CCR frequency analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…They suggested that the coronal index might be treated as one of the basic parameters of solar activity. The wavelet power spectrum of Minarovjech et al (2008) exhibited a prominent presence of a contour of amplitude ≈27 days in the GCR data set and other solar parameters, like coronal lines, Mg II core to wing ratio index from 1957-2004. Our investigation showed peaks of ≈16 and ≈30 days in both coronal Fe lines and the 10.7-cm solar radio flux, which is consistent with the results obtained by Kane (2003) in the same data set.…”
Section: Discussionmentioning
confidence: 93%
“…They suggested that the coronal index might be treated as one of the basic parameters of solar activity. The wavelet power spectrum of Minarovjech et al (2008) exhibited a prominent presence of a contour of amplitude ≈27 days in the GCR data set and other solar parameters, like coronal lines, Mg II core to wing ratio index from 1957-2004. Our investigation showed peaks of ≈16 and ≈30 days in both coronal Fe lines and the 10.7-cm solar radio flux, which is consistent with the results obtained by Kane (2003) in the same data set.…”
Section: Discussionmentioning
confidence: 93%
“…MWSI should seemingly lead the three indexes by about one rotation period, but such a lead is of statistical significance just for TSI. MCI is an energy-related index that represents the average irradiance (power) emitted by the green corona (Minarovjech et al 2011), and its time series may resemble the long-term variation of the corona energy, namely the variation of temperature at a certain layer of the corona. The phase relation between TSI, MCI, and large-scale solar magnetic activity reveals that there should be a certain mechanism which heats the photosphere and corona synchronously, so that their long-term variation maintains such a relation consistently.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Daily records of the following 14 solar activity indexes are used to investigate phase relation among them: SSN a and sunspot area b from 1874 May 9 to 2013 Dec 31, the adjusted 10.7-cm radio flux from 1947 March 5 to 2013 Dec 31 measured by Ottawa/Penticton 1 , flare index from 1966 Jan 1 to 2008 Dec 31 1 (Atac 1987), daily mean values of both the equivalent width of the helium 1 083-nm solar absorption line and the absolute line-of-sight magnetic field strength averaged over solar disk which are both measured by NSO/Kitt Peak from 1977 Jan 1 to 2003 Sept 21 1 , Ca ii 393.3-nm core-to-wing ratio (Ca ii index) observed by the Solar-Stellar Irradiance Comparison Experiment from 1991 Oct 3 to 1994 Sept 30 1 , X-ray intensity at 1–8 measured by the Geostationary Operational Environmental Satellite (GOES) from 1992 Jan 1 to 2001 Dec 31 1 , modified coronal index (MCI) constructed on the basis of ground-based measurements of the intensities of the coronal line 530.3 nm from 1943 Jan 1 to 2012 Dec 31 c (Lukac & Rybansky 2010; Minarovjech et al 2011), daily mean values of both the interplanetary magnetic field and solar wind velocity measured by various spacecrafts near the Earth’s orbit from 1963 Nov 27 to 2013 Dec 31 given by OMNIWeb 1 , daily occurrence number of coronal mass ejections (CMEs) from 1996 Jan 11 to 2013 June 30 listed in the SOHO/LASCO CME CATALOG d , Mg ii core-to-wing ratio (Mg ii index) from 1978 Nov 17 to 2007 Oct 24 1 (Heath & Schlesinger 1986; Viereck & Puga 1999), and the PMOD composite of TSI from 1978 Nov 17 to 2007 Oct 24 1 (Frohlich 2006). They are shown in Figure 1.…”
Section: Phase Relationship Of Long-term Solar Activitiesmentioning
confidence: 99%